Levator Ani avulsion: The histological composition of this site. A cadaveric study. Issue 1 (30th October 2018) - Da Silva, Ana Sofia; Asfour, Victoria; Digesu, Giuseppe Alessandro; Cartwright, Rufus; Fernando, Ruwan; Khullar, Vik
Abstract : Introduction: The sonographic appearance of a levator muscle "avulsion" representing the literal detachment of the pubovisceral muscle (PVM) enthesis has been contested. The nature of the levator ani "avulsion" is still not fully understood. It is known, that the tensile strength of a tendon is dependent on collagen with increased synthesis of collagen occurring in tissue with increased mechanical load levels. This study aims to perform a quantitative histological evaluation of the PVM enthesis with or without the imaging finding of levator ani "avulsion" to determine if there is a difference in the proportion of muscle and collagen. Method: Three‐dimensional translabial ultrasound for PVM "avulsion" was performed on cadavers using a GE Voluson I with a 5‐9 MHz electronic probe. Cadavers were meticulously dissected to identify the presence or absence of an anatomical avulsion. The PVM enthesis was excised for further histopathological processing and treated with three different colorations. Quantitative analysis using ImageJ software was conducted to compare tissue composition in samples with or without sonographic "avulsion." All stages were performed by two separate investigators blinded to each other's results. The results were analyzed using SPSS v24, IBM. Results: Twenty‐three PVM enthesis with histological staining were procured. Ultrasonographic "avulsions" were seen in 5/23 PVM enthesis. No anatomical avulsions were seen. There was no difference in the overall muscle or collagen content (Kruskal‐Wallis, P  = 0.864). The mean organized skeletal muscle content was 23% in the sonographic "avulsion" group versus 62% in the no "avulsion" group (Kruskall‐Walis, P  = 0.02). "Avulsions" were associated with a disorganized appearance at histology. Conclusion: The tissue composition relating to the proportion of muscle and collagen was not significantly different in specimens with or without sonographic "avulsions." However, morphological differences were observed in the organization of the muscle fibres, which requires further evaluation.